Investigation of mitochondrial DNA genetic diversity and phylogeny of goats worldwide - Yi GUO; Ying GONG; Yong-meng HE; Bai-gao YANG; Wei-yi ZHANG; Bo-er CHEN; Yong-fu HUANG; Yong-ju ZHAO; Dan-ping ZHANG; Yue-hui MA; Ming-xing CHU; Guang-xin E (Journal of Integrative Agriculture, 2022)
Genetic diversity, population structure, and population expansion of goats worldwide (4 165 individuals from 196 breeds) were analyzed using published mitochondrial DNA (mtDNA) D_loop hypervariable region sequences. Results showed that 2 409 haplotypes and 301 polymorphic sites were present within the 401-bp length D_loop region, the nucleotide diversity (Pi) was 0.03471, and the haplotype diversity (Hd) was 0.9983. Phylogenetic analysis revealed that 98.92% of haplotypes were divided into six obvious clusters, consistent with the classification of the known mitochondrial haplogroups of goats. Haplogroup A accounted for the largest proportion (86%). Interestingly, two unknown divisions (Unknown I and Unknown II) were discovered from goats in Southwest China, suggesting that Southwest China has unique maternal haplogroups. Analysis of molecular variance (AMOVA) and the average number of pairwise differences between populations (PiXY) indicated that geographical variation was small but significant. Neutrality tests (Tajima's D and Fu's FS tests) and mismatch distribution showed that haplogroups B, C, and G had expansion histories. In addition, the phylogenetic relationship between domestic and wild goats suggested that Capra aegagrus is the most likely wild ancestor and may have participated in the domestication of ancestral populations of A, B, C, and F haplogroups. A meta-analysis on the mtDNA sequences of goats from international databases was conducted to analyze goats’ genetic diversity, population structure, and matrilineal system evolution worldwide. The results may help further understand the domestication history and gene flow of goats worldwide.